Determination of stress-strain curve for microelectronic solder joint by ESPI measurement and FE analysis - Lee, BW; Jeong, JH; Jang, W; Kim, JY; Kim, DW; Kwon, D; Nah, JW; Paik, KW (WORLD SCIENTIFIC PUBL CO PTE LTD, 2003)
Many thermomechanical reliability studies on microelectronics and microsystems have relied upon computational analysis, since experimental work is rather difficult and very time-consuming. For computational analysis, it is essential to use as input accurate material properties; if not, the results of a reliability analysis may be very inaccurate. However, it is still quite difficult to arrive at unified material properties for modeling microelectronic assemblies because of the absence of standards for micro-material characterization, the difference between bulk and in-situ material properties, and so forth. The goal of this study was to determine the uniaxial stress-strain curve of a solder in a flip-chip assembly, using experimental measurements and finite-element analysis (FEA) of the solder's thermal deformation characteristics with increasing temperature. The thermal deformation of flip-chip solder joints was measured by electronic speckle pattern interferometry (ESPI). For the scale of evaluation required, the measurement magnification was modified to allow its application to micromaterials by using a long-working-distance microscope, iris and zoom lens. Local deformation of solder balls could be measured at submicrometer scale, and stress-strain curves could be determined using the measured thermal deformation as input data for finite-element analysis. The procedure was applied to an Sn-36Pb-2Ag flip-chip solder joint.